Kepemimpinan Instruksional Kepala Sekolah dalam Penguatan Manajemen Sekolah Dasar - Dilla Desfrita Wahyuni; Rika Novita; Detri; Yetty Morelent; Erwinsyah Satria (STKIP Subang, 2026)
The instructional leadership of school principals plays a strategic role in strengthening elementary school management, particularly in improving the quality of learning. This study aims to describe and analyze the role of instructional leadership of school principals in strengthening elementary school management. The research uses a qualitative approach with a case study design. The research subjects include principals and classroom teachers. Data collection was conducted through in-depth interviews, observations, and documentation studies. Data analysis was carried out interactively through the process of data reduction, data presentation, and conclusion drawing. The results show that the instructional leadership of principals contributes significantly to strengthening learning management, teacher professional development, and the formation of a school culture oriented towards learning quality. Principals play an active role in planning, implementing, and evaluating learning through academic supervision and continuous teacher mentoring. However, the implementation of instructional leadership still faces challenges in the form of time constraints and the administrative burden on principals. This study concludes that the instructional leadership of school principals is a key factor in realizing effective and sustainable elementary school management. The findings of this study are expected to serve as a reference for the development of elementary school leadership practices in an effort to improve the quality of education